(untitled) (The Conference Hub, 2026)
This article substantiates the content and sequence of work on the types of monologue speech of students: the stages of work are outlined, the techniques and the system of exercises are substantiated. The role of regional studies texts in the formation of monologue and dialogue speech is examined. The country text in this work is understood not traditionally, that is, not only as a text about the country of the language being studied, but also as a text about the country of students studying a non-native language, in this case about Uzbekistan.